Kate [large type] : the future queen - Nicholl, Katie (Thorndike Press, a part of Gale, Cengage Learning, 2013)
From her decade-long courtship with Prince William, to their fairy-tale wedding and rejuvenation of the monarchy, Kate Middleton has enchanted the public and media alike. How has this once shy, middle-class girl made such an effortless transition from commoner to royal? Nicholl brings her fascinating story to life, in order to reveal the truth about her past, her friends, her family, and, most crucially, the decisions she has made along the way that have radically shaped her future.